If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 3x(r + -1x) Y = (r * 3x + -1x * 3x) Y = (3rx + -3x2) Solving Y = 3rx + -3x2 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 3rx + -3x2
| z=xlny | | 231-(2x-6)=103 | | -4.9x^2+73=85 | | z=2x^2y-8xy^2+x^2+y^2 | | 10x+100=7x+39 | | 4.9x^2-73t+85=0 | | 9a+3=39 | | 2(2x+9.5)=12 | | z=ln(x^2+y^2) | | 5p+4=8p-2 | | 231-(x-6)=103 | | 3(x+2)+5(x+1)= | | 12x^2-72x+92=0 | | 294893+828= | | x^4+x^2-199=0 | | 4x^2-15+13=5x+4 | | z=cos(ax+by) | | 70-5(x-3)=45 | | x^3-5x^2+7x-2=0 | | x(2+6)=40 | | (6x-3)-(4-x)=5 | | x^2-3x-8=8x+4 | | 2X^2(2-x)-x(2x^2-5)= | | 2x=0+1 | | 7+78x=52x+15 | | -logx=3.17 | | x^2+y^2+3x-5y-25=0 | | x+.0825x=2000 | | 4(-3x-5)=-16 | | 5+6x=-20+x | | -3x+8=-9x+26 | | 203-v=255 |